Tax Rate not the Right Lever for Targeted Relief - Katja Rietzler (Wirtschaftsdienst)
Abstract With the current high inflation, bracket creep is back on the agenda. The federal government has introduced a bill to compensate for this effect, among other things, by shifting income tax brackets. In the debate on bracket creep, the point of reference is very important. Results differ greatly depending on the period and the income concept considered. Moreover, the income tax burden must be seen in the context of the overall fiscal policy. The decision on tax rate adjustments is a political issue.